Shaken Baby Syndrome as a Form of Abusive Head Trauma - Al-Saadoon, Muna (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2011)
Shaken baby syndrome (SBS) is a form of abuse that is characterised by brain injury. Because of the subtle and yet debilitating neurobehavioural impairment which ensues, SBS represents a diagnostic dilemma for attending clinicians. The situation is made worse by the young age of the affected child who may not be capable of explaining what happened. SBS has been reported in many parts of the world. To our knowledge, there is a dearth of literature on the topic from Arab/Islamic countries. This article attempts to shed light on the syndrome by reviewing information on the aetiology of SBS, as well as on its diagnosis and the reasons for delayed diagnosis. The central aim of this review is to increase awareness of SBS so that enlightened policies for prevention and intervention could be developed in the region and particularly in Oman.